Biorefinery—inspired, two-step valorization strategy to manage plant-based recalcitrant organic waste, involving solvent extraction, and fermentation with Bacillus clausii—a proof of concept study - Meppoyilam, Sreejith; Madhavan, Ajith; Bose, Chinchu; Pooja, Jayasree; Suresh, Swetha; Nair, Bipin G.; Pal, Sanjay (Frontiers in Microbiology, 2025)
Approximately 40–50% of municipal solid waste is organic and causing biogenic malodor and infections, due to inefficient treatment methods. Biorefinery-based bioremediation and valorization is in vogue against these conventional strategies since it combines unit operations for better efficiency and productivity. Deriving inspiration, the proposed strategy puts together a unique and compatible combination of processes. This novel two-step valorization workflow involves the extraction of small molecules using organic solvents, and fermentation of resulting denatured residues (increased biodegradability or decreased recalcitrance) of reduced microbial load. The extraction step also doubles up as a sterilization event, with different solvents (petroleum ether, chloroform, ethyl methyl ketone and methanol) exhibiting varied efficiency, methanol and ethyl methyl ketone being the most effective. Different recalcitrant plant organic wastes resulting from four plants (Cocos nucifera, Allium cepa, Artocarpus hirsutus and Swietenia mahagoni) were used as feedstocks in the preliminary exploratory study using chosen pathogenic bacteria. Onion peel (Allium cepa) ethyl methyl ketone extract was chosen for further studies, as it inhibits Salmonella enterica, which is associated with infection and malodour (due to biogenic H2S) in wastewater. Further, fractionation of the extract yielded quercetin and its glycoside. The onion peel residue, after solvent extraction was fortified with peptone and essential minerals to promote the growth of Bacillus clausii. Fortified post-extraction residue supported the growth better than the pre-extraction residue. The residue resultant after solvent extraction was fermented with Bacillus clausii and with release of bioactive supernatants. The concentrated supernatant showed significant inhibition of Salmonella enterica and Shigella dysenteriae. Additionally, all the exudates showed considerable inhibition in H2S production, respectively.